Effect of Board size on Earnings quality of Non-Financial Firms Listed at the Nairobi Securities Exchange - Kangea, Sammy Thuo; Nasieku, Tabitha; Muturi, Willy (Finance & Economics Review, 2022)
Purpose: The main purpose of the study was to analyze the relationship between board size and the earnings quality of non-financial firms listed on the Nairobi Stock Exchange (NSE) and also determine the effect of board size on earnings quality with ownership concentration as moderating variable. Methods: A positivist research philosophy was adopted and a quantitative research design was employed. The target population of the study was the 39 non-financial companies listed in NSE as of 31st December 2020. Secondary data was the main source of information for the study. The data was s panel type of data based on a period of 13 years (2008-2020). Positivism research philosophy and quantitative research design were employed in the study. Data were analyzed based on the panel regression model. Both diagnostic and specification test for the model applied was conducted. Results: The study established that board size had a significant effect on the earnings quality of non-financial firms listed at the NSE in the presence and absence of ownership concentration as moderator. Further, the results showed that the model with a moderator was superior to that without a moderator. Implications: The non-financial firms listed in NSE should closely examine the criteria used in determining the size of the board and its composition to ensure that boards are more independent and diversified. This will reduce incidences of earnings manipulations and ensure that the directors are accountable to the shareholders which in turn will lead to improvement of investor confidence.